2008
DOI: 10.1182/blood.v112.11.2157.2157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Donor/Recipient Major ABO Mismatch on Allogeneic Transplantation Outcome According to Stem Cell Source: Results from An 809-Patient Retrospective Study.

Abstract: ABO incompatibility between donor and recipient is not considered a barrier for successful allogeneic hematopoietic stem cell transplantation (HSCT). However, it is well established that major ABO incompatibility is associated with several immunohematological complications such as delayed hemolysis, delayed erythropoiesis, pure red cell aplasia and prolonged transfusion requirements due to the persistent presence of host-derived antibodies. Nevertheless, conflicting data still exist as to its influence on graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 24 Previous authors have suggested that BM, more than PBSC, affects red blood cell engraftment in major ABO-I transplants. 26 In our patients, BM graft predicted the delay of erythroid recovery at multivariate analysis. In addition, when analyzed by graft type, the major ABO-I group had longer RBC transfusion dependence in BM but not PBSC transplant.…”
Section: Discussionmentioning
confidence: 61%
“… 24 Previous authors have suggested that BM, more than PBSC, affects red blood cell engraftment in major ABO-I transplants. 26 In our patients, BM graft predicted the delay of erythroid recovery at multivariate analysis. In addition, when analyzed by graft type, the major ABO-I group had longer RBC transfusion dependence in BM but not PBSC transplant.…”
Section: Discussionmentioning
confidence: 61%